AUTOMATED ANALYSIS OF FEATURE MODELS: CHALLENGES AHEAD. - Batory, Don; Benavides, David; Ruiz-Cortés, Antonio (Communications of the ACM, 2006)
The article discusses computer software development, particularly the addition of features to an existing product. Research shows that feature models can be reduced to propositional formulas to make an analysis of their efficacy easier. When analyzing the benefits and drawbacks of feature addition, programmers should examine their impact on model consistency and performance scalability. The use of model-driven development and artificial intelligence configurators by programmers is detailed.